Rejection analysis and performance prediction of tubular membranes for dissolved salts Ausscheidungsanalyse und Leistungsvorhersage von tubulären Membranen für gelöste Salze - Qadir, D. (John Wiley and Sons Inc, 2022)
A detailed investigation of the performance of commercially available tubular membranes is carried out under varying operating conditions. Trans-membrane pressure, feed concentration, and cation types were chosen to study their effects on the membraneâs performance. Commercially available tubular membranes AFC80, AFC 30, ES404, and PU608 were selected. Aqueous solutions of varying ionic strength (2500 ppm, 5000 ppm,10000 ppm) of three salts, sodium chloride, magnesium chloride, and lead chloride were filtered to measure the permeate flux and rejection of selected tubular membranes. The AFC80 membrane had better rejection among all selected tubular membranes for all types of salts tested here. It is deduced that selected membranes carried a negative surface charge, which played a vital role during the separation mechanism. Finally, rejection of lead chloride and sodium chloride aqueous solutions was predicted accurately using the Spiegler-Kedem model with R2 reaching 0.9. Â© 2022 Wiley-VCH GmbH.